(untitled) (International Journal of Business Innovation, 2023)
The main objective of this work is to analyze, through a bibliometric study, the evolution and dynamics of scientific production on the relationship between corporate governance and tax management. We base our analysis on 322 articles from Scopus and ISI Web of Science published between 1998 and 2021. The difficulty of accessing confidential information means that most studies focus on tax planning and tax avoidance rather than tax evasion practices. Thus, tax avoidance is the most used expression to refer to tax management and, excluding the general expression corporate governance, the most used corporate governance mechanisms in the keywords are CEO, ownership structure, and board. However, political connections and gender are two expressions that have attracted more interest from researchers in the last three years. Most studies and the most influential are by authors affiliated in the USA, China, and Australia, and more research still needs to be carried out on samples of European companies. In addition, most studies use metrics to quantify tax management applied to the reality of US companies with a tax system different from the European one. This study contributes to the knowledge about the most studied tax management practices and the most related governance mechanisms, allowing the identification of clues for future research.